2021
DOI: 10.1177/15357597211018688
|View full text |Cite
|
Sign up to set email alerts
|

Perineuronal Net Dynamics in the Pathophysiology of Epilepsy

Abstract: Perineuronal nets (PNNs) are condensed extracellular matrix (ECM) assemblies of polyanionic chondroitin sulfate proteoglycans, hyaluronan, and tenascins that primarily wrap around GABAergic parvalbumin (PV) interneurons. During development, PNN formation terminates the critical period of neuroplasticity, a process that can be reversed by experimental disruption of PNNs. Perineuronal nets also regulate the intrinsic properties of the enclosed PV neurons thereby maintaining their inhibitory activity. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 75 publications
1
42
0
Order By: Relevance
“…Under aging and pathophysiological conditions the integrity and composition of the brain ECM undergo extensive changes, leading to a disturbed equilibrium of ECM production and deposition on one hand and ECM cleavage and clearance on the other hand ( Ulbrich et al, 2021 ). In human epilepsy as well as in rodent epilepsy models manifold ECM remodeling phenotypes have been reported in the brain tissue, with a particular focus on PNN disruption due to increased proteolysis, which may contribute to epileptogenesis (summarized in Dityatev et al (2010) , Chaunsali et al (2021) ). In histochemical analyses of postsurgical specimen from focal cortical dysplasia patients, known for a longstanding epilepsy with a high seizure burden, a complete reorganization of the ECM was reported with reduced brevican expression and disturbance of extracellular space diffusion parameters ( Zamecnik et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under aging and pathophysiological conditions the integrity and composition of the brain ECM undergo extensive changes, leading to a disturbed equilibrium of ECM production and deposition on one hand and ECM cleavage and clearance on the other hand ( Ulbrich et al, 2021 ). In human epilepsy as well as in rodent epilepsy models manifold ECM remodeling phenotypes have been reported in the brain tissue, with a particular focus on PNN disruption due to increased proteolysis, which may contribute to epileptogenesis (summarized in Dityatev et al (2010) , Chaunsali et al (2021) ). In histochemical analyses of postsurgical specimen from focal cortical dysplasia patients, known for a longstanding epilepsy with a high seizure burden, a complete reorganization of the ECM was reported with reduced brevican expression and disturbance of extracellular space diffusion parameters ( Zamecnik et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study measured PNN degradation and found that seizures lead to shifts in expression of PNN components, including HPLN1 ( Mcrae et al, 2012 ), which may be due to release of matrix metalloproteinases following status epilepticus ( Dzwonek et al, 2004 ; Dubey et al, 2017 ). However, a human postmortem study of PNN degradation after epilepsy did not show dysregulation of PNNs ( Rogers et al, 2018 ), which may be dependent on the PNN markers examined and timing following seizures (reviewed in Chaunsali et al, 2021 ). Consequently, it is not clear whether PNNs degrade similarly in humans or whether the degradation is transient and potentially stabilizes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Many PV-INs are ensheathed by perineuronal nets (PNN) (Wen et al, 2018;Carceller et al, 2020; Figure 6A), extracellular matrix (ECM) assemblies that can be easily detected by lectins such as the Wisteria floribunda agglutinin (WFA). PNNs regulate the intrinsic properties of the encapsulated neurons and thus aid the fast-spiking of PV-INs (Chaunsali et al, 2021). The loss of PNNs has been associated with diseases such as Alzheimer (Crapser et al, 2020) and epilepsy (Tewari et al, 2018;Chaunsali et al, 2021).…”
Section: Perineuronal Network Decrease In Kcc2 Ko Pv Micementioning
confidence: 99%
“…PNNs regulate the intrinsic properties of the encapsulated neurons and thus aid the fast-spiking of PV-INs (Chaunsali et al, 2021). The loss of PNNs has been associated with diseases such as Alzheimer (Crapser et al, 2020) and epilepsy (Tewari et al, 2018;Chaunsali et al, 2021). Notably, WFA signals per area were drastically decreased in the hippocampus and in the somatosensory and retrosplenial cortex of 23-week-old KCC2 KO PV mice (Figure 6B).…”
Section: Perineuronal Network Decrease In Kcc2 Ko Pv Micementioning
confidence: 99%